2011
DOI: 10.1039/c0cc01169j
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the antipodal series in microbial arene oxidation: a novel diene rearrangement induced by tricarbonyliron(0) complexation

Abstract: A cyclohexadiene ligand prepared by microbial arene 1,2-dihydroxylation undergoes spontaneous rearrangement upon complexation to tricarbonyliron(0). Subsequent iron removal affords a novel route to formal arene 2,3-dihydroxylation products enantiomeric to those obtainable by direct microbial arene oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 47 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…We had previously concluded that the formation of 20 arose via "clockwise" migration of the acetonide, rather than "anticlockwise" migration of the ester. 14 The absence of any such rearrangement in the case of bromodiene 12 is in keeping with this conclusion. The presence of the bromine in 12 also retards the rate of complexation with respect to unsubstituted analogue 15-identical reaction conditions result in consumption of all of 15, but recovery of 60% unreacted 12 (Scheme 7).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…We had previously concluded that the formation of 20 arose via "clockwise" migration of the acetonide, rather than "anticlockwise" migration of the ester. 14 The absence of any such rearrangement in the case of bromodiene 12 is in keeping with this conclusion. The presence of the bromine in 12 also retards the rate of complexation with respect to unsubstituted analogue 15-identical reaction conditions result in consumption of all of 15, but recovery of 60% unreacted 12 (Scheme 7).…”
Section: Resultssupporting
confidence: 63%
“…Most notably a diene possessing the ortho-meta pattern of oxygenation found in 2 but antipodal to 2 may be accessed from 4 by means of such organoiron complexes. 14 The unique synthetic versatility of 4 has thus been demonstrated. However, we sought to enhance further the utility of the BZDO-mediated benzoate dihydroxylation by use of substituted benzoate substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In the event, a product was isolated in which the iron was indeed coordinated to the upper diene face, but in which a rearrangement had occurred, conjugating the ester to the diene and giving 77. 20 We rationalise this result through initial formation of the expected product 78 and its subsequent co-ordination of an unknown Lewis acidic species to give 79. C-O bond scission would then afford cationic cyclohexadienyl complex 80.…”
Section: Organometallic Chemistrymentioning
confidence: 65%
“…[1][2][3][4][5][6][7] Although the clear majority of synthetic examples are derived from diols obtained by the Toluene Dioxygenase enzymatic complex, dienediol 1 obtained by the ipso, ortho cisdihydroxylation of benzoic acid by Benzoate Dioxygenase (expressed in the mutant Ralstonia eutropha B9) has been recently used by several research groups to produce biologically active natural products and/or advanced intermediates. (Scheme 1A) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Examples are found in the literature for the total synthesis of polyoxygenated materials from benzoic acid, such as (-)-idesolide, [10] (+)-grandifloracin, [9] piperenol B, [13] pleiogenone A [14] and, more recently, a formal approach to xylosmin and flacourtosides E and F. [20] Although the dienic system in 1 does not present any substituent to allow for the differentiation of both olefins, selective oxygenation of either center of the ring can be accomplished by selecting the appropriate sequence of reactions (osmylation, epoxidation, diol protection) as described by Myers et al in 2001. [25] Regarding the preparation of N-containing products, several examples are shown in the literature, such as the synthesis of inosaminoacids, [26] inosamines, [7] pyrrolidines, [12] and tetracyclines [8] from benzoic acid ( Figure 1A).…”
Section: Graphical Abstractmentioning
confidence: 99%